(untitled) (Journal of Hama University, 2022)
The study aimed to identify the level of multiple intelligences and its relationship to academic achievement among the fourth graders, and it also aimed to test the significance of the differences between average intelligence (linguistic, logical, visual, kinesthetic, musical, social, personal) according to the gender variable, and to achieve these goals the curriculum was used. Analytical descriptive through the application of the Multiple Intelligences Scale directed to fourth-grade students, and the scale was limited to (42) phrases, to measure the types of intelligences adopted in the study, which are intelligence (linguistic, logical, kinesthetic, visual, musical, social, personal) and academic achievement was also measured according to Five Scale: (excellent, very good, good, average, poor) The study was applied to a sample of the fourth grade students, which numbered (376) male and female students, during the first semester of 2020 year.The level of multiple intelligences came to a medium degree, and that the most common intelligence among fourth-grade students is intelligence: linguistic with a high degree and an arithmetic average (3.84), followed by a logical with a high degree and an arithmetic mean (3.25), then a visual with a medium degree and an arithmetic average (2.51), then the kinesthetic With a medium score and an arithmetic mean (2.50), then a social with a medium score and an arithmetic mean (2.49), followed by a musician with a low score and an arithmetic mean (2.22), and finally the personal with a low score and an arithmetic mean (1.76). It was also found that there is a relationship between academic achievement and intelligence (linguistic, logical), and there is no relationship between academic achievement and intelligence (kinesthetic-visual-musical-social-personal), and there are statistically significant differences between the type of intelligence (linguistic, logical). (kinesthetic-visual-musical-social - personal) according to gender (males/females) and the differences are in favor of (males).